Rumen fluke in cattle and buffaloes in Asia: a review - Ahmad Tookhy, Nazir; Nur-Mahiza, Md Isa; Mansor, Rozaihan; Yasmin, Abd Rahman; Ahmad, Nur Indah; Hamzah, Noor Hazfalinda; Idri, Lokman Hakim (Universiti Putra Malaysia, 2022)
Rumen fluke is a parasitosis that infects ruminant animals across a wide geographical range of countries. It is a severe infection in temperate and tropical climate regions of Asia, Australia, Africa, and Europe, which cause significant economic losses. In this review, the available information to date on rumen fluke species infecting cattle and buffaloes in Asian countries is evaluated. The citation search was performed through specific keywords, literature published from 1964 to 2021, retrieved from electronic databases: Scopus, Web of Science, Pub Med, Education Resources Information Center (ERIC), Science Direct, Elsevier, and Google Scholar. Twenty-six (26) rumen fluke species belonging to two families: Paramphistomidae 61.5% (16/26) and Gastrothylacidae 38.4% (10/26), were reported in cattle and buffaloes in fourteen Asian countries. Paramphistomum cervi and Cotylophoron cotylophorum are the most prevalent species with broader distribution in countries than the other genera. The coprological prevalence varies from 0.8% to 98.17% and 0.86% to 78.4% in cattle and buffaloes, respectively. The prevalence of rumen fluke by fluke counts method range between 6.45% to 90.6% and 4.29% to 75.07% in cattle and buffaloes, respectively. The sedimentation method and fluke count are reliable tests for detecting rumen fluke in live and slaughtered animals. In conclusion, the rumen fluke should be considered a critical production disease that affects cattle and buffaloes in Asia. Further studies are necessary to determine the rumen fluke-snail associations, develop diagnostic tests to detect prepatent infections in the definitive host, determine the economic importance of rumen fluke, and determine the efficacy of different anthelmintic in the treatment of patent infections in the definitive host.